1982
DOI: 10.1007/bf01908167
|View full text |Cite
|
Sign up to set email alerts
|

Calcium movements in relation to heart function

Abstract: SumtnaryIt is widely recognized that calcium is of singular importance in the viability of the myocardial cell, nonetheless little is known concerning the precise nature of the action of calcium in myocardium as to how it maintains the life of the cell and how it may dictate the death of the cell. However, recent advances in research involved with the study of calcium movement in the heart have been highly valuable for the formulation of new concepts with respect to the physiological and pathological aspects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
2

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(74 citation statements)
references
References 114 publications
4
68
0
2
Order By: Relevance
“…Since streptozotocin-induced diabetes in rats is associated with loss of body weight, it can be argued that the observed changes in cardiac phospholipid methylation are due to the catabolic effect of diabetes. Because our experiments with weight-matched as well as weight-and age-matched control animals showed values for the phospholipid methylation (26). The Ca2+ plus ATP-induced effect on phospholipid methylation was also seen in liver and skeletal muscle microsomes, where it was suggested to be mediated by a calmodulin-dependent regulatory system (24,25).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Since streptozotocin-induced diabetes in rats is associated with loss of body weight, it can be argued that the observed changes in cardiac phospholipid methylation are due to the catabolic effect of diabetes. Because our experiments with weight-matched as well as weight-and age-matched control animals showed values for the phospholipid methylation (26). The Ca2+ plus ATP-induced effect on phospholipid methylation was also seen in liver and skeletal muscle microsomes, where it was suggested to be mediated by a calmodulin-dependent regulatory system (24,25).…”
Section: Discussionmentioning
confidence: 55%
“…It has been shown that PE methyl transfer reaction starts on the cytoplasmic side of the membranes where cytosolic AdoMet is available to donate methyl groups (3). Therefore, in the beating heart cell, phospholipid methylation can be seen to occur in the presence of cytosolic levels of free Ca2" ranging from -lO-' M during rest to lO-' M in response to excitation (26). (l0-7 to l0-4 M) plus 10 ,gM ATP on the PE N-methylation activity at 0.055 ,uM AdoMet (site I, where PMME is specifically synthesized) in cardiac SL, SR, and mitochondria from control and diabetic hearts.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of Ca 2+ that enters the cell is a major determinant of the concentration of Ca z+ at the myofilaments during systole, and is a major determinant of the level of contactile force as a result [26]. In fact, ATP-independent Ca2 § in heart sarcolemma has been shown to exhibit linear relationship with the contaetile force development in the normal myocardium [24][25][26][27][28].…”
Section: A Tp-independent Ca2*-bindingmentioning
confidence: 99%
“…Depressed Ca2' uptake by the sarcoplasmic reticulum as well as alterations in Ca2+-activated ATPase have been demonstrated for sarcoplasmic reticular and myofibrillar fractions from diabetic rat hearts (5,6). In view of the importance of the movement of extracellular Ca2+ across the myocardial membrane in modulating the contractile performance of the heart (7,8), it is possible that alterations in trans-sarcolemmal Ca2`flux may participate in this cardiomyopathy. This hypothesis has been indirectly supported by a preliminary study in which an abnormal response of isolated heart preparations from diabetic animals to extracellular Ca2' was found (9).…”
Section: Treatment Of Sarcolemma With Neuraminidase Decreased Ca2+mentioning
confidence: 99%